Optimización del proceso de destilación mediante una columna empacada, para la obtención de pájaro azul, en la parroquia Facundo Vela, provincia Bolívar - Andrade Viscarra, Bryan Eugenio (2024)
The present research work is responsible for analyzing two types of packaging such as ceramic and stainless steel Raschig rings in a distillation column to obtain a rectified alcohol. For this purpose, the base alcohol of 30° and 40° GL alcoholic strength is analyzed, which chemically contains: Furfural 1.06 and 1.96 mg/100 cm3, Methanol 5.01 and 4.03 mg/100 cm3, Higher alcohols 254.37 and 250.25 mg/100 cm3. The design of the packaging column has the following measurements: total height 85 cm and packaging height 18 cm. T4:R2 was determined as the best treatment with a yield of 67% and a final graduation of 80º GL, which has a filling of 152 rings of 2cm * 2cm type of ceramic Raschig rings. The rectified alcohol was used to prepare a traditional drink from the area called Pájaro Azul with a standardized formulation. The product obtained was subjected to a chemical analysis to determine the presence of congeners in which the following values are reported: alcoholic strength 40 GL, Furfural <0.01 mg/100 cm3AA, Methanol 0.70 mg/100 cm3AA, Higher alcohols 1.29 mg/100 cm3AA, Congeners 1.29 mg/100 cm3AA, the product obtained complies with the mandatory Ecuadorian technical standard INEN 338 for production and consumption of alcoholic beverages.